Group psychological counseling to contrast academic burnout: a research protocol for a randomized controlled trial - Messina, Irene; Rossi, Tatiana; Bonaiuto, Flavia; Granieri, Gianluigi; Cardinali, Paola; Petruccelli, Irene; Maniglio, Roberto; Loconsole, Claudio; Spataro, Pietro (Frontiers in Psychology, 2024)
Academic burnout is a condition characterized by exhaustion, cynicism, a distant attitude toward studying, and diminished self-efficacy in academic activities. Preliminary scientific findings indicate that interventions designed to alleviate work burnout also hold promise for mitigating academic burnout, however clear evidence based on randomized controlled trials is still missing. This research protocol describes a randomized controlled trial aimed at evaluating the efficacy of an online group psychological intervention to contrast academic burnout. Participants with high levels of burnout will be assigned to a psychological counseling group or a waiting list control group. The research comprises several phases: (T0) Screening, Recruitment, and Randomization; (T1) Baseline assessment (pre-intervention); (T2) Outcome Assessment (post-intervention); (T3) Follow-up Assessment (3 months post-intervention). The primary outcomes include burnout symptoms, general well-being, and academic achievement. Additionally, secondary variables such as effort-reward imbalances, satisfaction/frustration of basic psychological needs, intrapersonal and interpersonal emotion regulation, coping strategies, and social support will be examined. The psychological intervention strategies will encompass psychoeducation, self-awareness enhancement, cognitive restructuring, and promotion of social support. This research protocol is an initial step toward evidence-based psychological interventions to treat academic burnout.